PENGARUH PENGUNGKAPANCORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN - Yani, Widya (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to test the influence of Corporate Social Responsibility disclosure to the Return on Equity and Stock Return in the manufacturing companies which are listed in the Indonesia Stock Exchange. Quantitative research is the type of research which is used in this research by emphasizing on the research variable test with figures and by performing data analysis with statistics procedures. Independent variable which is applied in this research is the Corporate Social Responsibility. The dependent variables apply Return on Equity and Stock Return.The samples of this research are the secondary data from the Indonesia Stock Exchange which is the annual report of manufacturing companies which are listed in 2009-2011. The samples are selected by using purposive sampling method with the determined criteria. As much as 26 companies per years or 78 per firm years are selected by using the above criteria.The simple linear regression analysis is applied in this research with statistics t test as hypothesis. Based on the result of t test between CSR and ROE variable are found to have significant value as much as 0.032 which means the first is accepted. The result of t test between CSR and Stock Return variable are found to have significant value as much as 0.038 which means the second hypothesis is accepted. The result of this research indicates that the implementation of Corporate Social Responsibility has significant positive influence to the Return on Equity and Stock Return. This condition describes the disclosure of Corporate Social Responsibility is getting better which reflects the company performance is getting better as well.Keywords: corporate social responsibility, return on equity, stock return.